Wawasan Pengembangan Kebijakan Pendidikan - Eqlimah, Eqlimah (Maliki Interdisciplinary Journal, 2025)
Educational policy plays a strategic role in shaping the quality of human resources in Indonesia. The need for an adaptive, responsive, and sustainable education system is increasingly urgent in the context of globalization and technological advancement. This study discusses the definition, characteristics, principles, objectives, and directions of educational policy as regulated in Law No. 20 of 2003 on the National Education System. The findings show that educational policy must have clear objectives, legal formality, operational aspects, be subject to evaluation, and be formulated by authorized parties. Principles of humanity, justice, and sustainable development serve as the foundation. The direction of policy emphasizes equal access, teacher quality improvement, system and curriculum reform, and institutional strengthening. However, its implementation still faces challenges, particularly at the elementary level, which is crucial to the success of national education.